Evaluation of the biological control by the yeast Torulaspora globosa against Colletotrichum sublineolum in sorghum - Rosa, Marcia Maria [UNESP]; Tauk-Tornisielo, Samia Maria [UNESP]; Rampazzo, Pedro Eduardo; Ceccato-Antonini, Sandra Regina (Springer, 2010)
The yeasts are microorganisms with great potential for biotechnological applications in diverse areas. The biological control of phytopathogens by yeasts has showed satisfactory results under laboratory conditions, and it has already produced commercial formulations. With this as focus, this work aims to perform in vitro and in vivo evaluations of the action of a Torulaspora globosa yeast strain (1S112), isolated from sugarcane rhizosphere, against the phytopathogenic mold Colletotrichum sublineolum, the causative agent of anthracnose in sorghum. In vitro experiments included the antagonism test in Petri dishes with morphological hyphal evaluation; yeast killer activity; siderophore, volatile compound and hydrolytic enzyme production. In vivo experiments were conducted in greenhouse conditions with a sorghum variety susceptible to C. sublineolum by evaluating the anthracnose disease for 6 weeks. The results indicated that the yeast strain significantly controlled the fungal growth, either in vitro or in vivo. The strain of T. globosa exhibited killer activity against two sensitive strains, which is a novel capacity for this species. The yeast did not produce siderophores, volatile compounds or hydrolytic enzymes, although it has reduced the mycelial growth, resulting in hyphal deformities but not cell death. The yeast controlled the anthracnose disease in sorghum, either inoculated before or after the fungal spores, suggesting that the competition for space and nutrients to dominate the mold and killer toxin production, altering the hyphal morphology, are mechanisms utilized by the yeast in the biocontrol.
Keywords: Biological control; Yeasts; Torulaspora globosa; Colletotrichum sublineolum; Killer yeast